2000
DOI: 10.1006/dbio.2000.9679
|View full text |Cite
|
Sign up to set email alerts
|

nhr-25, the Caenorhabditis elegans Ortholog of ftz-f1, Is Required for Epidermal and Somatic Gonad Development

Abstract: We have analyzed the expression and function of the Caenorhabditis elegans gene nhr-25, a member of the widely conserved FTZ-F1 family of nuclear receptors. The gene encodes two protein isoforms, only one of which has a DNA binding domain. nhr-25 is transcribed during embryonic and larval development. A nhr-25::GFP fusion gene is expressed in the epidermis, the developing somatic gonad, and a subset of other epithelial cells. RNA-mediated interference indicates a requirement for nhr-25 function during developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(163 citation statements)
references
References 59 publications
8
155
0
Order By: Relevance
“…Interestingly, inhibition of nhr-23, nhr-25, and lrp-1 gene expression also resulted in some morphological abnormalities. All these genes, including cpz-1, are highly expressed in the major hypodermal cells in all larval stages of nematodes, which supports their involvement in epidermal differentiation during or after molting (45,46,48).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Interestingly, inhibition of nhr-23, nhr-25, and lrp-1 gene expression also resulted in some morphological abnormalities. All these genes, including cpz-1, are highly expressed in the major hypodermal cells in all larval stages of nematodes, which supports their involvement in epidermal differentiation during or after molting (45,46,48).…”
Section: Discussionmentioning
confidence: 60%
“…Control mechanisms that regulate such a complicated process are poorly understood, but recent studies have implicated two C. elegans nuclear hormone receptors (NHR-23 and NHR-25) in the regulation of molting (45)(46)(47). Molting defects were observed after interference with C. elegans nhr-25 gene expression by RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…qua-1(gk32) causes developmental arrests at the L1/L2 stage with a high penetrance (98%). This early arrest is in contrast to other molting mutants such as lrp-1, nhr-23, and nhr-25 that exhibit molting defects in all four larval stages (Kostrouchova et al, 1998;Yochem et al, 1999;Gissendanner and Sluder, 2000). Observation of the arrested qua-1 mutant larvae reveals that molting is defective.…”
Section: Deletion Mutant Qua-1(gk32) Causes Molting Defectsmentioning
confidence: 81%
“…So far, the regulatory mechanisms of C. elegans molting are not yet understood, although about a dozen genes have been identified that lead to molting defects when mutated. These genes can be classified into five categories based on their possible functions: (1) proteases that are used to degrade the old cuticle, including a cathepsin Z-like cysteine protease (Cecpz-1) (Hashmi et al, 2004), and two metalloproteases, nas-36 and nas-37 (Davis et al, 2004;Suzuki et al, 2004); (2) transcriptional regulators, including nhr-23 (Kostrouchova et al, 1998(Kostrouchova et al, , 2001, nhr-25 (Asahina et al, 2000;Gissendanner and Sluder, 2000), and let-19 (Wang et al, 2004); (3) enzymes involved in cholesterol metabolism such as let-767 (Kuervers et al, 2003) or cholesterol transporters such as lrp-1 (Yochem et al, 1999); (4) molecules involved in secretion and extracellular transport such as sec-23 (Roberts et al, 2003) and CeVps-27 (Roudier et al, 2005); (5) others, such as the angiotensin converting enzyme-like non-peptidase acn-1 (Brooks et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As observed in insects, expression of nhr-23 and nhr-25 mRNAs oscillates with each molting cycle (Gissendanner et al, 2004) and RNAi of both receptors at the intermolt results in a defective molt, with associated problems of cuticle shedding (Ashaina et al, 2000;Gissendanner and Sluder, 2000). However, whereas HR3 controls the expression of FTZ-F1 in insects, nhr-25 expression seems not dependent of nhr-23 (Krostrouchova et al, 2001).…”
Section: Bgftz-f1 Controls Moltingmentioning
confidence: 97%